INTERACTIVE SENSOR TECHNOLOGIES IN THE TRAINING OF ATHLETES OF THE CHILDREN'S DEPARTMENT OF THE STUDENT SPORTS CLUB - Vasyuk V.E. ,; Ren Yichen,; Bakaev V.V. ,; Karaseva T.V. ,; Lukashevich D.A. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to substantiate the effectiveness of the use of interactive sensory technologies in motor-cognitive training of young athletes. Methods and structure of the study. Taekwondo athletes aged 11-12 (n=45) from the children's department of the sports club of the Belarusian National Technical University took part in the scientific work. A sample of athletes was formed with a random division into the control (n=22) and experimental group (n=23). The control group trained according to the standard program using traditional training aids, and the athletes of the experimental group additionally trained twice a week for two months according to the program using training aids based on interactive sensory technologies. Results and conclusions. The results of the study showed that the practice of performing training tasks in conditions close to the specifics of a sport using sensor technologies makes it possible to achieve positive changes in the development of the motor-cognitive potential of athletes at the stages of early sports improvement. The results obtained allow us to conclude that the use of sensory technologies in controlled interactions of athletes is of high practical value, which reflects significant improvements in the performance of the participants in the experiment in all key parameters characterizing the effectiveness of motor actions in test tasks with different coordination complexity.